2013
DOI: 10.1017/s1751731112002169
|View full text |Cite
|
Sign up to set email alerts
|

Impact of fibre intake and fibre source on digestibility, gut development, retention time and growth performance of indigenous and exotic pigs

Abstract: The impact of fibre level and fibre source on digestibility, gastrointestinal tract (GIT) development, total tract mean retention time (MRT) and growth performance was studied in indigenous Mong Cai (MC) and exotic Landrace 3 Yorkshire (LY) pigs. The diets were based on maize, rice bran, soyabean meal, fish meal and soyabean oil, and cassava residue (CR) or brewer's grain (BG) as fibrous ingredient sources in the high-fibre diets (HF) and were fed ad libitum. A low-fibre diet (LF), containing around 200 g NDF/… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
27
0
1

Year Published

2014
2014
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 29 publications
(29 citation statements)
references
References 28 publications
1
27
0
1
Order By: Relevance
“…Other studies showed similar trends (Len et al, 2009b;Ngoc et al, 2013). Khieu et al (2005) with Mong Cai found a higher digestibility by local breeds but only for the fibre fraction of the feed.…”
Section: Forage Utilisation By Pigsmentioning
confidence: 56%
See 3 more Smart Citations
“…Other studies showed similar trends (Len et al, 2009b;Ngoc et al, 2013). Khieu et al (2005) with Mong Cai found a higher digestibility by local breeds but only for the fibre fraction of the feed.…”
Section: Forage Utilisation By Pigsmentioning
confidence: 56%
“…The results of a literature overview on the comparison of indigenous and improved breeds regarding TTAD and DM intake when fed on fibre-rich diets are displayed in Table 5. When Zimbabwean Mukota (Ndindana et al, 2002) and Vietnamese Mong Cai (Ngoc et al, 2013) were compared with Large White pigs, those breeds showed no difference in intake levels when fed a high-fibre diet. However, in other studies, Mong Cai pigs consumed more (70 v. 60 and 85 v. 78 g/kg metabolic BW) compared with improved pigs (Landrace × Yorkshire) (Len et al, 2009a and2009b).…”
Section: Forage Utilisation By Pigsmentioning
confidence: 94%
See 2 more Smart Citations
“…This scheme is rationalized by the recent study showing better feed digestibility in Mong Cai than exotic pigs (Ngoc et al 2013). That a number of households also produce pure-bred Mong Cai is reassuring in terms of the requirement for replacement sows.…”
Section: Discussionmentioning
confidence: 99%